Rice tungro bacilliform virus encodes reverse transcriptase, DNA polymerase, and ribonuclease H activities. - Laco, G S (1994)
Rice tungro bacilliform virus (RTBV) is a newly described badnavirus and proposed member of the plant pararetrovirus group. RTBV open reading frame 3 is predicted to encode a capsid protein, protease (PR), and reverse transcriptase (RT) and has the capacity to encode other proteins of as yet unknown function. To study the possible enzymatic activities encoded by open reading frame 3, a DNA fragment containing the putative PR and RT domains was used to construct the recombinant baculovirus PR/RT-BBac. Trichoplusia ni insect cells infected with PR/RT-BBac were used in pulse-labeling experiments and demonstrated synthesis of an 87-kDa polyprotein that corresponds in molecular mass to that predicted from the PR/RT DNA coding sequence. The 87-kDa polyprotein was processed with concomitant accumulation of 62-kDa (p62) and 55-kDa (p55) proteins. Amino-terminal sequencing of p62 and p55 determined that they mapped to the PR/RT domain and shared common amino termini. p62 and p55 were purified and exhibited both RT and DNA polymerase activities using synthetic primer/template substrates. Only p55 had detectable ribonuclease H activity, an activity intrinsic to all reverse transcriptases studied to date. Characterization of the RTBV RT provides a biochemical basis for classifying RTBV as a pararetrovirus and will lead to further studies of these proteins and their role in virus replication.